A Review of Recycling Status of Decommissioned Lithium Batteries - Chen, Yaodong; Dou, Aichun; Zhang, Ye (Frontiers in Materials, 2021)
This review analyzes the current global use of lithium batteries and the recycling of decommissioned lithium batteries, focusing on the recycling process, and introduces the status of domestic and foreign recycling industry of decommissioned lithium batteries.It also points out the existing problems and the prospects for the future development of the decommissioned lithium batteries recycling in China.